2017
DOI: 10.1177/0731684417732840
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of machining parameters of composites using multi-attribute decision-making techniques: A review

Abstract: An in-depth literature survey of machining study on fiber-matrix composites is presented in this review paper. The review work mainly focuses on optimization of machining parameters in composite materials with different machining factors. Conventional machining processes such as turning, drilling and milling as well as composite materials which are reinforced with fibers are considered in this study. Machining aspects on various fiber matrix composites has been carried out over a long period of time. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Polymers, composites, and metals are used as work components, tool geometry, and material as cutting tool factors. [168] In-plant fiberreinforced polymer composites, only a few investigations are present. Zajac et al [169] identified the effect of feed and rotation speed on the surface roughness during turning in wood polymer composites.…”
Section: Turning Of Plant Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…Polymers, composites, and metals are used as work components, tool geometry, and material as cutting tool factors. [168] In-plant fiberreinforced polymer composites, only a few investigations are present. Zajac et al [169] identified the effect of feed and rotation speed on the surface roughness during turning in wood polymer composites.…”
Section: Turning Of Plant Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…Therefore, the optimization of process parameters is important in the drilling of CFRP to performance in an effective manner [137]. This can help in giving the best drilled-hole quality and better drill tool life in a more useful manner [138].…”
Section: Optimization Of Process Parametersmentioning
confidence: 99%
“…The turning process deliberates on different constraints such as feed rate, speed, and cutting depth as machining parameters; metals, composite materials, and polymers as work materials; and tool material and tool geometry as cutting tool parameters as shown in Figure 15. 146…”
Section: Processing Of Nfrcsmentioning
confidence: 99%